KEPERCAYAAN DIRI ANAK JALANAN DI SEKITAR LAMPU MERAH GRAMEDIA PEKANBARU - Putri, Fika Sasqia; Rosmawati, Rosmawati; Donal, Donal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: this research aims to describe the characteristics and how the self confidence of street children around the red light of gramedia pekanbaru. This research used qualitative approach with type of descriptive research to describe the characteristics and self confidence of street children clearly. The subjects in this study were 6 children who were taken by accidental sampling technique. Data analysis technique was used are observation and structured interviews. The result of this study showed street children aged 7-14 years, still attending school in primary and secondary school, lived with their parents, doing these activities to help their parents, increase their pocket money, and to spend leisure time. Self confidence of street children around the red light of gramedia pekanbaru was good based of indicators self belief, brave, and positive attitude.Keyword: characteristic, street children, self confidence